Curriculum as place: The social relevance of the secondary school curriculum in Jamaica. Issue 2 (21st June 2020) - Roofe, Carmel
Abstract : A socially relevant curriculum connects learning to the needs of students as members of families, communities and society. Curriculum as place is concerned with experience; how the curriculum nurtures students' learning, growth and development and how they in turn make meaning of what they are learning given their situatedness. This study, therefore, sought to explore students' views on how their school curriculum influenced their engagement at the personal, family and community levels thereby making it socially relevant. Data from interviews of 27 high school students provide thick descriptions of participants shared views and are used to theorise about how the curriculum influenced students' engagement. The main findings indicated that students' perception of what curriculum is, influenced their interpretation of how their curriculum experiences facilitated their engagement and this interpretation was linked to their situated agency. The findings also underscored the role of the curriculum as a critical tool for creating social consciousness and destroying coloniality of knowledge. Using the findings of the study, the author argues that for society to change and for curriculum to be socially relevant the purposes of the curriculum must facilitate agency and social consciousness at three levels; personal; family and community.